English as a Medium to Foster Scientific Diversification through International Community Service Program - Fabianto, Eko; Nurusysyifa, Nisa’a; Sasha, Vira Adoria (LPPM Universitas Pancasakti Tegal, 2025)
This study investigates how English functions as both a communicative and academic medium in fostering scientific diversification through the International Community Service Program at Institut Bakti Negara (IBN) Tegal, Central Java, Indonesia. In an era of globalized higher education, equipping students with global competencies—such as English proficiency, intercultural adaptability, and interdisciplinary collaboration—has become increasingly vital. Using a qualitative case study approach, the research explores the experiences of students involved in International Community Service Program in Malaysia and Thailand between 2023 and 2024. Data were obtained through interviews, observations, documentation, and focus group discussions. The findings show that English was used not only in everyday interactions but also in conducting academic activities such as workshops, presentations, and community-based research. Students developed stronger academic communication skills, broadened their cultural understanding, and engaged in interdisciplinary teamwork. These outcomes enriched institutional curriculum and produced student-led outputs, including teaching modules and reflective reports. However, challenges related to language anxiety and cultural adjustment were observed, indicating the need for targeted institutional preparation. Ultimately, the program highlights the value of English-mediated service learning in enhancing students' academic and global capacities. The results also underline the broader significance of international community engagement as a pathway for educational innovation and social contribution.